Geo-spatial knowledge and intelligence. 4th International Conference on Geo-Informatics in Resource Management and Sustainable Ecosystem, GRMSE 2016, Hong Kong, China, November 18-20, 2016, Revised selected papers /: 4th International Conference on Geo-Informatics in Resource Management and Sustainable Ecosystem, GRMSE 2016, Hong Kong, China, November 18-20, 2016, Revised selected papers. Part I : (2017) - Unknown
No abstract available